Implementasi Sistem Informasi Kelurahan Pondok Pucung Berbasis Web Menggunakan Metode Prototype - Chaerunnisa; Bintang Seroja; Tia Kusuma Wardani (CV. Multi Kreasi Media, 2026)
Rapid advances in information technology have pushed government agencies to modernize their public service delivery through digital platforms. The Pondok Pucung Village Office currently relies on traditional channels—such as notice boards and in-person announcements—to communicate with residents, a practice that limits the reach and timeliness of information. This research seeks to develop a web-based information platform that consolidates village profile data, vision and mission statements, organizational hierarchy, public services, news updates, and contact details into a single accessible interface, enabling residents to obtain accurate information conveniently and without delay. The Prototype methodology was adopted to guide system development, ensuring continuous user participation across all stages—from needs assessment and initial prototype construction to iterative evaluation, revision, and final deployment. The technical stack comprises Next.js for the front-end layer, Express.js for back-end API services, MySQL for data persistence, and Vercel as the hosting solution. Functional verification was carried out through Black box testing to confirm that every system feature performs as intended. The outcome demonstrates that the developed system effectively delivers organized public information, enhances community access to village data, and streamlines content management for administrators. Comprehensive testing confirmed that all core functionalities operate correctly, establishing the website as a reliable and appropriate official information channel for the Pondok Pucung Village Office.